The effects and predictive values of novel anthropometric parameters on uric acid levels and hyperuricemia in adults - Li Hongwei; Shen Zhenhai; Jiang Wei; Jia Bing; Li Shaolei; Zhang Ping; Wang Liuyu; Yuan Peng; Lu Yun (Scientific Reports)
Abstract Novel anthropometric indices are more closely related to metabolic abnormalities than traditional anthropometric indices. Fewer studies have been conducted based on the relationship between novel anthropometric indicators and hyperuricemia. This study was to analyze the serum uric acid (SUA) levels of adults and the relationship between hyperuricemia and these new indicators in Su-Wuxi-Chang area of China, in order to provide a theoretical basis for the management of SUA levels in patients with hyperuricemia. A total of 14,834 adults were enrolled. The information of height, weight, waist circumference, lifestyle, fasting plasma glucose (FPG), lipids, and SUA were collected. The traditional obesity indices and novel anthropometric indices were calculated by formulas. Lipid accumulation product (LAP), triglyceride glucose (TyG) and body roundness index (BRI) are independent risk factors for hyperuricemia in both men and women (P < 0.001). In males, the predictive ability of LAP and TyG to the incidence of hyperuricemia were 0.694 and 0.661 in AUC area, respectively (P < 0.001) and which were 0.767 and 0.746 respectively in females (P < 0.001). In both men and women, the LAP and TyG indices were more predictive of hyperuricemia than the other indices (P < 0.001). The capacity of LAP and TyG indexes were better than other traditional anthropometric indexes in predicting hyperuricemia in this population. The predicted hyperuricemia ablity of LAP in both male and female better than other traditional and new anthropometric indicators.